Drusen classification in bilateral drusen and fellow eye of exudative age-related macular degeneration. - Hamada, S; Jain, S; Sivagnanavel, V; Patel, N; Chong, N (2006)
AIM: To assess the value of the modified international classification system in screening high-risk patients with bilateral age-related maculopathy (ARM) from those with lower risk characteristics. METHODS: In total, 164 digital images of 106 patients with either bilateral ARM (group A) or the fellow eyes of unilateral exudative age-related macular degeneration (AMD) (Group B) were included. Patients with no signs of ARM in both eyes or those with bilateral late AMD were excluded. The images were randomised and then graded by two masked ophthalmologists based on the modified International Classification of ARM. RESULTS: The interobserver consistency between the two graders was high with a Kappa value of 0.82 (SE 0.34, P<0.0001). There were no significant differences in the distribution of the stages of ARM between the two subgroups. Stage 3 was the most common stage in each group for both graders followed by stage 2a in the bilateral drusen group. Stages 1a, 2a and 2b were equally the next common stage in the fellow eye of chordial neovascularisation group. CONCLUSION: A screening system based on clinical characteristics would be of value in risk prediction in a clinical setting. Type of Drusen alone, as identified by the modified International grading system, may not be reliably predictive in screening for patients who are at high risk of developing choroidal neovascularisation.